The Analysis of Impacts for Knowledge Management in Higher Education Sector: The Case of Ikh Zasag International University, Mongolia - Dashdeleg, Magsarjav; Munkh-Undrakh, Baatarjav; Munkhsaruul, Baatarjav; Dulguunmandakh, Enkhbold (Advances in Social Sciences Research Journal, 2024)
The primary purpose of our research is to examine the relationships between academics’ capability skills, attitudes and communication skills toward knowledge management. We worked on this study using basic management theory and social science to establish work assumptions and new conceptual models that international researchers employed in their research. The poll was done online by 133 professors, allowing us to classify and compare some of the results. We used SMART PLS-3.0, a qualitative research tool, to evaluate correlational and multifactorial data, as well as to present the findings of the forensic scientist’s investigation of how factor variables affect knowledge management. Our research has the potential to be significant in addressing both theoretical and practical concerns, as well as implementing additional most necessary practices at Ikh Zasag International University in Mongolia.